SUPERVISOR SUPPORT, MEANINGFUL WORK, AND HAPPINESS IN EMPLOYEE ENGAGEMENT - Tarek, Brenda Stefani Novelia; Muzakki, Muzakki; Herachwati, Nuri (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2025)
The furniture manufacturing industry plays a crucial role in the global economy, driven by changing consumer lifestyles, urbanization, and the rapid expansion of the property sector. As demand for high-quality and eco-friendly furniture rises, ensuring high team member engagement becomes essential for maintaining productivity and innovation. This study examines the impact of supervisor support, Meaningful Work, and happiness at work on team member engagement in the furniture industry. Using the Job Demands-Resources (JD-R) theory, this research explores how job resources enhance engagement by increasing motivation and reducing job demands. Data were collected through team member surveys in furniture companies and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that supervisor support, Meaningful Work, and happiness at work significantly influence team member engagement, with happiness at work emerging as the strongest predictor. This study contributes to the literature by integrating the JD-R theory within the furniture industry context. The findings suggest that organizations should implement strategies that foster team member happiness, create meaningful work experiences, and strengthen supervisor support to enhance engagement and overall performance.